Heavy metal concentration and health risk assessment in commonly sold vegetables in Dhaka city market - Sultana, M; Mondol, MN; Mahir, AA; Sultana, R; Elahi, SF; Afrose, N; Chamon, AS (Bangladesh Journal of Scientific and Industrial Research, 2019)
This study assesses the levels of heavy metals in vegetables (Cucumis sativus, Solanum lycopersicum, Ipomoea aquatica, Amaranthus cruentus, Basella alba, Brassica oleracea, Musa acuminata) collected from Kawran Bazar vegetable market located in Dhaka, Bangladesh. Also, it examines potential health risks from the consumption of these vegetables. The samples were randomly collected, processed and analyzed for heavy metals using Atomic Absorption Spectrophotometer. Among the vegetables Basella alba had the highest heavy metal content followed by Cucumis sativus, Amaranthus cruentus, Solanum lycopersicum, Brassica oleracea, Musa acuminate and Ipomoea aquatica. The average daily intake for Cr (0.245 mg/person/day) was above the permissible maximum tolerable daily intake of 0.20 mg/person/day endorsed by WHO/FAO (2013). The hazard quotient (HQ) values for Cd in Basella alba (4.400) and Brassica oleracea (1.333), for Cr in Ipomoea aquatica (1.756), Amaranthus cruentus (1.655), Basella alba (3.033) and Musa acuminate (1.333) as well as the hazard indices (HI) for I. aquatica (2.537), A. cruentus (2.791), B.alba (8.883), B. oleracea (2.295), M. acuminate (2.999) exceeded unity, signifying presence of health risks from consumption of the vegetables. This study recommends regular monitoring of heavy metals in vegetables and foodstuffs to prevent excessive accrual in food chain. Bangladesh J. Sci. Ind. Res.54(4), 357-366, 2019